Holographic Fermi Surface at Finite Temperature: Exploring the Existence of a Fermi Surface in a Dual Field Theory at Finite Temperature (Journal of Advances and Scholarly Researches in Allied Education, 2023)
The GaugeGravity duality allows us to effortlessly switch between a strongly coupled ddimensionalfield theory and a weakly connected d + 1 dimensional gravity theory. The powerful toolsmade accessible by the holographic duality may be useful in a variety of domains, including as gaugetheory, hydrodynamics, and condensed matter theories. The situation of low temperatures has beenincluded to our studies. The examination of the spectrum function of these fermionic modes supportsthe zero-temperature result. We find that at a certain temperature, only specific modes allow for a Fermisurface in a limiting version of this blackhole background with a single charge. If we extend the analysisperformed at zero temperature to the finite temperature situation, we will find the formula for thecomplete Green's function of the dual theory. In the dual field theory, scalars also have a significantimpact on whether or not a black hole with a single charge has a Fermi surface. Since the predictedvalue of the scalar in the dual fermionic operator is non-zero, we found that the Fermi surface may existthanks to the presence of dual operators.